2018
DOI: 10.5395/rde.2018.43.e46
|View full text |Cite
|
Sign up to set email alerts
|

Improved dentin disinfection by combining different-geometry rotary nickel-titanium files in preparing root canals

Abstract: ObjectivesThis study was to evaluate the antibacterial effect of different instrumentation and irrigation techniques using confocal laser scanning microscopy (CLSM) after root canal inoculation with Enterococcus faecalis (E. faecalis).Materials and MethodsMesiobuccal and mesiolingual canals of extracted mandibular molars were apically enlarged up to a size 25 hand K-file, then autoclaved and inoculated with E. faecalis. The samples were randomly divided into 4 main groups according to the system of instrumenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 39 publications
2
22
0
5
Order By: Relevance
“…In the present study regarding the control groups 5 specimens did not receive CGM to ensure that the analysis of cleaned canal did not yield false positive of residual CGM, likewise, 5 specimens received CGM without subsequent removal to assure that CGM was uniformly present in the simulated IRR cavities and that amount initially applied was significantly different from any amounts remaining after cleaning procedure in tested groups (25) In the present study , the complete removal of the colored gelatin material off the walls of the simulated IRR cavities was not obtained in any of the test groups (A,B) this was in accordance with previous studies (10,11,12,15,17 ) Regarding the results of the present study group A (cleaned using PUI) recorded a low Mean percentage of residual CGM at 16. 88% which comes in agreement with previous studies (4,5,6) Whom also found PUI to be an effective method of removing debris and smear layer , bacterial biofilm, intracanal medicaments in either normal canal configuration or simulated IRR cavities This may be due to the irrigation agitation which creates more intense shear forces with in the fluids in root canal which increases the irrigant penetration into the tissues and through the root canal and may explain the efficacy in flushing out CGM from IRR cavities as previously described by Jiang et al (26) .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study regarding the control groups 5 specimens did not receive CGM to ensure that the analysis of cleaned canal did not yield false positive of residual CGM, likewise, 5 specimens received CGM without subsequent removal to assure that CGM was uniformly present in the simulated IRR cavities and that amount initially applied was significantly different from any amounts remaining after cleaning procedure in tested groups (25) In the present study , the complete removal of the colored gelatin material off the walls of the simulated IRR cavities was not obtained in any of the test groups (A,B) this was in accordance with previous studies (10,11,12,15,17 ) Regarding the results of the present study group A (cleaned using PUI) recorded a low Mean percentage of residual CGM at 16. 88% which comes in agreement with previous studies (4,5,6) Whom also found PUI to be an effective method of removing debris and smear layer , bacterial biofilm, intracanal medicaments in either normal canal configuration or simulated IRR cavities This may be due to the irrigation agitation which creates more intense shear forces with in the fluids in root canal which increases the irrigant penetration into the tissues and through the root canal and may explain the efficacy in flushing out CGM from IRR cavities as previously described by Jiang et al (26) .…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the agitation and activation of the irrigation in group B which leads to turbulence in the irrigation and amplifies its action with in the root canal as previously reported by Alves etal (35) who observed a drop in bacterial count in infected root canals after application of XP-endo finisher Likewise XP-endo finisher was shown to be superior in removing smear layer and hard tissue debris from root canal walls in studies by Leoni etal (32) and Elnaghy etal (16) furthermore this may be attributed to the use of combination of instruments ( XP-shaper and Finisher) compared to a single instrument PUI which comes in accordance with similar findings by Abdelhady etal 2018 (36) who showed that the combined use of XP and PUI together was more efficient in removing smear layer than each instrument used separately and which is consistent with results of Bedier etal (11) whom found the combination of XP shaper and finisher was significantly more efficient in removing E Faecalis from root canals than when used alone. however, results from the present study disagrees with those shown by Keskin etal (15) who found no significant difference between XP and PUI in removing intracanal medicaments from resorpative defects And Wigler et al (37) who also showed no significant difference between XP-finisher and PUI in removing calcium hydroxide from artificial grooves in the apical third of root canal Which was also confirmed by Uygun et al (38) .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present finding that root canals instrumented with the XP-endo Shaper allowed a more frequent (76%) optimal obturation result, according to the above criteria, may be explained by previous ex vivo studies of this adaptive file. The ability of this file to adequately instrument and clean the canals of permanent teeth with an oval cross-section has been studied using microCT [ 20 , 27 , 31 , 32 ]. It has been demonstrated that the XP-endo Shaper resulted in better 3D instrumentation than rotary files, affecting a higher percentage of the root canal walls [ 20 , 27 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Embora o preparo biomecânico reduza o contingente bacteriano, a desinfecção completa do SCR é dificultada devido à sua complexidade anatômica (MACHTOU, 1980;HAAPSALO et al, 2014;GRAYSON, 2016;SILVA et al, 2017;BEDIER;HASSAN, 2018). Portanto, o uso das soluções irrigadoras é indispensável, visto que conseguem atingir áreas de difícil acesso, onde os instrumentos não conseguem tocar (ALKAHTANI; AL-KHUDHAIRI; ANIL, 2014;KONSTANTINIDI et al, 2017) como canais laterais, istmos e ramificações apicais WESSELINK, 2001;BERGENHOLTZ, 2003, NAIR et al, 2005GANAHL;PETERS, 2009;METZGER et al, 2010;ALVES et al, 2011;ZANDI et al, 2016;DUQUE et al, 2017).…”
unclassified